Variations Of Seawater Properties Of The Southwestern Coastal Waters Of The Caspian Sea - Jamshidi, Siamak (2012)
The Caspian Sea is the largest inland saltwater body in the world, but only a few studies have been conducted on the variations of seawater properties in its southern coastal waters. This study carried out to determine seawater properties and sea currents for the purpose of investigating the stratification in water column and interactions among the physical, water quality, and biological components of the seawater properties. Field measurements were conducted using two methods: CTD probe profiling deployed once during each of the four seasons (i.e., winter, spring, summer, and autumn) and using current meter. The collected data were analyzed using polynomial functions and cubic interpolation techniques in Matlab programming and regression modeling. Results showed that the significant changes in seawater properties occurred primarily within the upper 100 m layer. The seawater temperatures recorded were 9–11 °C (March), 18–19 °C (April), 27–29 °C (August), and 19–20 °C (November) near the surface. A seasonal thermocline was detected between 20 and 50 m depth in summer at a temperature gradient of 16 °C. The subsequent destruction of the thermocline layer occurred with the general cooling of the surface water and deepening of the mixed layer toward the end of autumn and winter. The mean value of the seawater salinity was 12.33 ppt which its lowest and highest values were recorded in March and August, respectively. The variations in seawater density within the upper 100 m layer were considerable (between 1005.78 and 1010.75 kg m-3), but below this layer, the value remained around 1010 kg m-3. The vertical variations in density agree with variations of temperature in water column, and a pycnocline was observed at the location of the thermocline. The maximum speed of sound in seawater was observed at the surface layer, between 1517–1519 m s–1 in August. This value decreased to about 1453 m s–1 below 450 m.